2016
DOI: 10.1007/s40279-016-0579-9
|View full text |Cite
|
Sign up to set email alerts
|

Utility of S100B Serum Level for the Determination of Concussion in Male Rugby Players

Abstract: S100B measured 36 h after a match is thus a discriminating test to identify concussion in a male rugby player, with a 100 % negative predictive value.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(11 citation statements)
references
References 28 publications
1
10
0
Order By: Relevance
“…The early acute elevations of brain injury biomarkers observed in the current work are consistent with prior studies of SRC or other forms of mild TBI (mTBI). For example, elevated S100B and UCH‐L1 have been reported in multiple samples of athletes with SRC and in emergency department (ED) patients with mTBI . Current results also extend prior work demonstrating the potential utility of alpha‐II‐spectrin breakdown products for the acute assessment of brain injury .…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…The early acute elevations of brain injury biomarkers observed in the current work are consistent with prior studies of SRC or other forms of mild TBI (mTBI). For example, elevated S100B and UCH‐L1 have been reported in multiple samples of athletes with SRC and in emergency department (ED) patients with mTBI . Current results also extend prior work demonstrating the potential utility of alpha‐II‐spectrin breakdown products for the acute assessment of brain injury .…”
Section: Discussionsupporting
confidence: 71%
“…Blood‐based biomarkers have been a focus recently because of their relative cost‐effectiveness and their potential as point‐of‐care markers. Biomarkers that putatively capture various aspects of the neurometabolic cascade of concussion have been investigated following SRC, including S100 calcium binding protein B (S100B), glial fibrillary acidic protein (GFAP), ubiquitin c‐terminal hydrolase‐L1 (UCH‐L1), alpha‐II‐spectrin derivatives, and general inflammatory markers . As highlighted in a recent systematic review, however, much of the prior blood biomarker work in SRC has been limited to relatively small sample sizes and/or did not include preseason (ie, preinjury) assessments .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Previous work has attributed change of S100B levels to various factors besides frank concussion, including subconcussive head impacts, physical exertion, and non-brain injury. 16,19,23,24,31,32 Nevertheless, this study provides both cross-sectional and longitudinal evidence of elevated S100B levels measured at 6 h following SRC.…”
Section: Discussionmentioning
confidence: 71%
“…While several of the included studies apply to sports involving physical contact (170)(171)(172)(173), and as such do not apply to older individuals at risk of AD, other studies have found evidence of increased S100β in activities that may be undertaken by older adults. S100β levels were found to increase following running possibly due to repeated striking of the ground causing repeated subtle head trauma (173).…”
Section: The Impact Of Physical Activity On S100β Levelsmentioning
confidence: 99%